Adaptasi Sosialbudaya dalam Adopsi Pertanian Sawah dan Konsekuensinya terhadap Pangan Rumbia. Kasus Orang Taboso, Maluku Utara - Agus Salim Bujang (Yayasan Literasi Sains Indonesia, 2025)
Changes in the potential and resources of the internal and external environment are situations that require the cultural response of the Taboso people to adapt in various ways. The study, entitled, “Sociocultural adaptation in the adoption of paddy farming and its consequences for sago palm food (metroxylon sagu), in the case of the Taboso people, West Halmahera, aims to explain: first, the factors underlying the adoption of paddy farming; second, sociocultural adaptation; and, third, its cosequences for sago palm as a food source. The research, cunducted from January 2022 to December 2024, used in-depth interviews, observations, group interviews, households cencus, rice food availability survey, and utilized written historical sources regarding Taboso people’s agriculture. The results show that cultural interest shaped by economic conditions, uncertainty, and the associative meaning of rice food underlie their adoption of paddy farming, even before the introduction of the national paddy field printing program in 2016. Consequently, there was a conversion of land and sago palm into paddi fields covering an area of 363 hectares. Family konship institutions and communal land ownership functionally play a role in adaptation by accomodating the paddy farming system to meet cultural needs for food.